Achalasia and chronic opiate use: innocent bystanders or associated conditions?. Issue 1 (21st January 2015) - Ravi, K.; Murray, J. A.; Geno, D. M.; Katzka, D. A.
Summary: High‐resolution manometry identifies three subtypes of achalasia. However, type 3 differs from classic achalasia. Although opiates affect esophageal motility, opiate use and achalasia have not been studied. Patients with a new diagnosis of achalasia at Mayo Clinic Rochester between June 1, 2012 and January 3, 2014 were identified. Clinical records were reviewed to assess symptoms, opiate use, and therapy. Fifty‐six patients with achalasia were identified, 14 (25%) were on opiates. Opiate prescription was unrelated to achalasia in all cases, with chronic back and joint pain constituting the majority. Of patients on opiates, five (36%) had type 3 achalasia compared with four (10%) not on opiates ( P = 0.02). No patients on opiates had type 1 achalasia. Clinical presentation did not differ with opiates, although those on opiates were more likely to report chest pain (39 vs. 14%, P = 0.05) and less likely to have esophageal dilation (62 vs. 82%, P = 0.13), none with greater than 5‐cm diameter. Contractile vigor was greater with opiate use, with distal contractile integral of 7149 versus 2615.5 mmHg/cm/second ( P = 0.08). Treatment response was inferior on opiates, with persistent symptoms in 22% compared with 3% without opiates ( P = 0.06). Opiate use is common in type 3 achalasia, with the majority of patients on opiates. No patients on opiates were diagnosed with type 1 achalasia. Manometric findings of type 3 achalasia mimic those induced by opiates, suggesting a physiologic mechanism for opiate induced type 3 achalasia. Treatment outcome is inferior with opiates, with opiate cessation perhaps preferable. Further studies assessing opiate use and achalasia are needed.